Influence of water-washed neem fruits (azardirachta indica A. juss) on heamatology and serum biochemical indices of West African dwarf sheep (2014)
Neem is a fast growing tree that thrives well in all parts of Nigeria. The seeds are readily available because the plant is used to control desertification. A 4 - week feeding trial was conducted to investigate the effect of supplementation of water - washed neem fruit (Azardirachta indica A.juss) in diets on haematological and serum biochemical indices of West African Dwarf (WAD) ewes. Three diets were formulated to contain water-washed neem fruit at graded levels of inclusion; 0% (control), 5% and 10%. Twelve 10 month old WAD ewes were randomly assigned to 3 dietary treatments. Each treatment had 4 replicates. Variations in values of haematological and serum biochemical parameters of WAD ewes fed experimental diets were determined. Some haematological parameters (RBC and Hb counts) measured were significantly (p<0.05) different while PCV, WBC, some differential counts and serum biochemical parameters were not significantly different among the treatments. However, urea, creatinine, glucose and alkaline phosphatase levels in serum of WAD ewes showed significant (p<0.05) differences, while, other serum biochemical indices measured were not significant. Although, the result of this study showed that the inclusion of water - washed neem fruit at 10% depressed some heamatological parameters, but showed no adverse effect on the ewes. However, all the values obtained for serum biochemical indices were within the normal physiological range except for alkaline phosphatase. Therefore, water - washed neem fruit can be included in the diet of WAD ewes at 10% without any deleterious effect.